A human laterality disorder associated with recessive CCDC11 mutation. Issue 6 (10th May 2012) - Perles, Zeev; Cinnamon, Yuval; Ta-Shma, Asaf; Shaag, Avraham; Einbinder, Tom; Rein, Azaria J J T; Elpeleg, Orly
Abstract : Background: Significant advancements in understanding the molecular pathophysiology of laterality determination were recently made. However, there are large gaps in our knowledge of the initial processes that lead to laterality defects, such as heterotaxy syndrome (HS, also known as situs ambiguous) and situs inversus totalis (SIT). The former refers to abnormal distribution of visceral organs, and the latter refers to a complete laterality inversion of both abdominal and thoracic viscera. Methods: In order to identify a mutated gene in SIT and HS patients, the authors performed homozygosity mapping in a consanguineous family with laterality disorders identified in two siblings. Results: A homozygous deleterious mutation in the CCDC11 gene was identified in the patients. The mutation resulted in an abnormally smaller protein in the patient's skin fibroblasts. The parents and five healthy siblings were heterozygous for the mutation, which was not present in 112 anonymous controls. Conclusions: Few genes have been associated with both SIT and HS, usually accompanied by other abnormalities. The authors suggest that CCDC11 is associated with autosomal recessive laterality defects of diverse phenotype resulting in SIT in one individual family member who is otherwise healthy, and in complex laterality anomalies (HS) in another member. This report underscores the importance of CCDC11 in laterality determination.